Multisystem Inflammatory Syndrome in Children (MIS-C), a Post-viral Myocarditis and Systemic Vasculitis—A Critical Review of Its Pathogenesis and Treatment - McMurray, Jeremy C.; May, Joseph W.; Cunningham, Madeleine W.; Jones, Olcay Y. (Frontiers in pediatrics, 2020)
MIS-C is a newly defined post-viral myocarditis and inflammatory vasculopathy of children following COVID-19 infection. This review summarizes the literature on diagnosis, parameters of disease severity, and current treatment regimens. The clinical perspective was analyzed in light of potential immunopathogenesis and compared to other post-infectious and inflammatory illnesses of children affecting the heart. In this paradigm, the evidence supports the importance of endothelial injury and activation of the IL-1 pathway as a common determinant among MIS-C, Kawasaki disease, and Acute Rheumatic fever.